Individual Coping Strategies Are Associated with Patient-Reported Satisfaction upon Completion of Rehabilitation following Sports-Related Knee Surgery - Everhart, Joshua S.; Harris, Kristie M.; Schiele, Steven E.; Abouljoud, Moneer; Eikenberry, Alexander; Emery, Charles F.; Flanigan, David C. (The Journal of Knee Surgery, 2019)
We sought to determine whether individual coping strategies and optimism are associated with satisfaction after sports-related knee surgery at the time of rehabilitation completion and whether the association between coping strategies/optimism and satisfaction varies by surgical procedure or length of rehabilitation. A total of 104 recreational and competitive athletes who underwent knee surgery completed preoperative assessments for intrinsic optimism using the revised Life Orientation Test and coping strategies using the brief Coping Orientations to the Problem Experience inventory. Postoperative assessments at completion of rehabilitation (mean: 5.5-month follow-up.; maximum: 15 months) included satisfaction with surgery, return to prior level of sport, and International Knee Documentation Committee (IKDC-S) symptom scores. Eighty-one percent were satisfied after completion of rehabilitation with a 68% return to prior level of sport. Irrespective of surgical procedure or length of rehabilitation (p > 0.25, all comparisons), greater reliance on others for emotional support as a coping mechanism increased risk of dissatisfaction after surgery (per point: odds ratio [OR]: 1.75; confidence interval [CI]: 1.13–2.92; p = 0.01), whereas greater use of positive reframing as a coping mechanism was protective (per point: OR: 0.43; CI: 0.21–0.82; p = 0.009). Intrinsic optimism was not predictive of postoperative satisfaction (p = 0.71). Satisfied patients had mean 13.5 points higher IKDC-S scores at follow-up than unsatisfied patients (p = 0.001). Patients who returned to prior level of sport had significantly higher satisfaction scores than patients who had not. Irrespective of surgical procedure or length of rehabilitation, use of positive reframing and reliance on others for emotional support are positive and negative predictors, respectively, of satisfaction after sports-related knee surgery. Preoperative optimism is not predictive of postoperative satisfaction.
Keywords: sports injury; knee surgery; coping strategies; threat perceptions; postoperative satisfaction